The Effect of Using Songs to Elevate Students’ Vocabulary Skill at SMP Yabes School - Hetty Zaharani (Journal of Classroom Action Research, 2023)
This study focuses on utilizing English songs as a means to enhance students' language skills and increase their motivation to learn English. The research aims to investigate the impact of song lyrics on expanding students' vocabulary. The study employs a quantitative research approach and involves one class of Seven-grade students from Yabes School, comprising 20 in the first semester of 2022-2023 academic year. The data collection instruments consist of pre-test and post-test assessments, which include fill-in-the-blank tests and multiple-choice questions. The findings reveal a significant improvement in vocabulary, as indicated by higher mean scores in the post-test (72) compared to the pre-test (45), resulting in a score increase of 27 points. This study concludes that the use of songs effectively enhances students' vocabulary acquisition by stimulating their learning process and fostering word memorization. The findings of the study indicate that the students perceived English songs as beneficial for their vocabulary learning, acquisition, and retention. The results demonstrated that the students believed that English songs had the ability to capture their interest in learning vocabulary. Furthermore, utilizing English songs assisted them in remembering the forms, meanings, and usage of the newly acquired vocabulary. Keywords: Vocabulary enhancement, Song lyrics, Language skills, Motivation, Language acquisition